Wave Reflection in the Solar Atmosphere - Varun Chaturmutha; Bernhard Fleck; Stuart M. Jefferies (The Astrophysical Journal, 2024)
We present evidence supporting wave reflection in the lower solar chromosphere based on helioseismic analysis of multi-height Doppler data from the Solar Dynamics Observatory/Helioseismic and Magnetic Imager and the Magneto-Optical filters at Two Heights II instrument. This evidence is derived through a wave propagation model that incorporates both upward- and downward-traveling (reflected) waves. Moreover, we find that the height of the reflecting region varies with magnetic field strengths in a way that suggests a connection with the plasma β ∼ 1 region. We measure an effective reflection coefficient of 13% in a magnetically quiet region of the Sun.